Management strategies to improve phosphorus use efficiency under an uncertain climate: a review - Cordeiro, Carlos Felipe dos Santos; Rosolem, Ciro Antonio (Frontiers in Agronomy, 2026)
Root growth is one of the main strategies to improve phosphorus (P) uptake from soils, but both root growth and P movement to the roots are impaired by soil water shortage. Several studies have evaluated the effect of P availability on root growth, as well as the impact of root growth on drought tolerance, but there is still a lack of unity in this knowledge. Thus, the objective of this review article is to identify the primary P management strategies that can enhance root growth and P acquisition in crops during dry spells. This review synthesizes studies published from 1963 to 2025, with emphasis on field-based experiments conducted under rainfed or water-limited conditions. For this purpose, articles carried out in different parts of the world were reviewed. Based on these studies, we found that the main challenge to improving P acquisition by plants under water stress is to enhance P availability in the soil subsurface, which remains wetter for a longer period. Broadcast application of P has been a problem mainly in rainfed and water-restricted environments, and application of P in the sowing furrow is recommended in these environments. The use of cover crops, crop-livestock integration, crop rotation, liming, adjustment of optimum pH, and increase of C and humic substances in the soil are important techniques to improve the availability and mobility of P in the soil and consequently the root growth and P uptake in depth. Plants and cultivars with larger root systems and especially long and dense root hairs can improve drought tolerance and PUE. Growth-promoting microorganisms can help in drought tolerance through better hormonal balance and root growth, but there is still a need for new knowledge associated with P solubilization under field conditions. Future research should seek to evaluate the interactive effects of the use of microorganisms, root growth, and drought tolerance with field studies in different production systems.